Sexual Violence on Religious Campuses - Vanderwoerd, James R.; Cheng, Albert (Canadian Journal of Higher Education, 2017)
Religious colleges and universities make up a substantial segment of the higher education landscape in North America, but the incidence of sexual violence on these campuses remains understudied. This study estimates the incidence of sexual violence on independent Christian campuses using a sample of part-time and full-time undergraduate students (N = 668) from eight private Christian colleges in Ontario, Canada. Using two widely used measures of sexual violence enabled comparisons with studies of self-reported incidents at secular and public colleges and universities. The findings show that 18% of women at religious colleges reported experiencing unwanted sexual contact within the past year, compared to studies of self-reported rates on secular campuses ranging from 21.4% to 31.4%. Exploratory investigation of factors related to victimization suggests that religious colleges may provide a “moral community” that could reduce the risk of sexual violence.